Karstmorphodynamik und ihre hydrologische Steuerung - Schmidt, Karl-Heinz (ERDKUNDE, 1979)
Process inter-relationships between precipitation and run off variables and dissolved sediment concentration (CaCO3; MgC03) were investigated in a limestone area (Iserlohner Kalksenke) in the northern Rheinische Schiefergebirge. Concentrations were analyzed for 26 sampling sites. Where significant correlations between dissolved sediment concentration and precipitation could be found, these were negative. The concentrations show the best correlations with the precipitation amounts of the preceding 10 days (N10) .Samples from karst springs show no significant correlation with precipitation data. The confidence levels for the correlations between dissolved sediment concentrations and discharge data are very high, the values of the exponents in the regression equation (C = aQb) lying between -0.15 and -0.25. When rates of solutional erosion are estimated, the variation of dissolved sediment concentration and dissolved sediment load with different magnitudes of discharge must be considered. The rate of chemical denudation was calculated for the study area using the rating curve and flow curve technique. The rate obtained is 29 m3/km2/a or 29 mm/1000 a.